An Energy-Based Safety Evaluation Index of Blast Vibration - Mingsheng Zhao; Dong Huang; Maosen Cao; En-an Chi; Jun Liu; Qiang Kang (Shock and Vibration)
The combined peak particle velocity (PPV) and frequency safety criterion for blast vibration is widely used in blasting engineering. However, some field investigations are inconsistent with this criterion. On the basis of field investigations, it is found that there are two failure modes of structures subjected to blasting seismic waves, that is, first-excursion failure and cumulative plastic damage failure. Moreover, the nature of structural responses under blast vibrations is a process of energy input, transformation, and dissipation. Therefore, an energy-based dual safety standard is proposed in this work to more comprehensively explain all failure modes of structures under blast vibrations. To this end, structures are simplified into elastic-plastic single degree of freedom (SDOF) systems with bilinear restoring force models, and energy responses of SDOF systems are then determined using the Newmark-β method. From the energy responses, the maximum instantaneous input energy and hysteretic energy are selected as the basis of the dual safety criterion, because they can reflect first-excursion failure and cumulative plastic damage failure, respectively. Finally, field investigations in a blasting site in Zunyi, Guizhou province, China, are used to prove that compared to the PPV-frequency criterion the proposed energy-based dual safety criterion is more capable of assessing the damage potential of blast vibrations.